Effect of Elevated Temperature and Ethyl Methane Sulfonate on the Growth and Yield Attributes of Summer Onion (Allium Cepa L) - Luhan, Asif Hasnath; Ali, Muhammad Aslam; Islam, Md Rafiqul; Auyon, Shah Tasdika; Rabbi, SK Md. Fazlay; Kundo, Deboki; Nitu, Tazbeen Tabara; Kabir, Humayun (Discoveries in Agriculture and Food Sciences, 2024)
Onion cultivation during summer wet season faces problems in seedlings raising and difficulties in management practices in the main field, which is a great concern. Ethyl methane sulphonate (EMS) is a chemical mutagen which helps to develop desirable mutant by point mutation. The present experiment was carried out at the Horticulture field laboratory of BINA, Mymensingh during the period July to October, 2019 to investigate the effect of ethyl methane sulphonate (EMS) for developing desirable mutants of onion under ambient and elevated temperature conditions. In this experiment five different doses of EMS viz., 0%, 0.5%, 1%, 1.5% and 2% were applied on onion seeds and the treated seedlings were grown under ambient and elevated temperature conditions. The experiments were conducted following Randomized Complete Block Design (RCBD) in field and Completely Randomized Design (CRD) in pot experiment under greenhouse condition. In the field trial, under ambient condition total leaf area, leaf area index, chlorophyll content and total bulb yield were significantly influenced by different concentrations of EMS. At ambient temperature, the highest bulb length (6.52 cm) and diameter (5.04 cm), single bulb weight (38.3 g) and total bulb yield (14.95 t/ha) were recorded with 0.5% EMS application, which decreased with further increasing concentrations of EMS (1.0-2.0%). On the contrary, the above yield parameters and total bulb yield were decreased under elevated temperature condition (+ 2ºC higher than ambient) irrespective of EMS concentrations. Above all, the interaction effects of temperature and EMS concentrations on onion seeds germination, seedling growth and yield components were found non-significant, although maximum total bulb yield was found with 0.5% -1.0% EMS application under ambient temperature condition. Conclusively, growth and yield attributes of summer onion were enhanced by applying chemical mutagen EMS at 0.5%-1.0% under ambient field condition, however elevated temperature (+2ºC higher than ambient) affected the yield of summer onion at all levels of EMS application.